Greening Urban Spaces: A Healthy Community Design - Liu, Hongxiao; Wu, Tong; Li, Yuan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The focus of this reprint is to draw attention to Greening Urban Spaces. Cities play a central role in advancing economic and social developments and addressing the challenges that humanity face today. Although cities provide access to better health services, urban life is also associated with factors that are deleterious to human health, such as increased stress, mental fatigue, pollution, as well as sedentary lifestyles and a disconnection to the natural environment. There is a growing consensus across many academic fields and health promotion policy areas that the provision of accessible and high-quality greenspace is a vital element in the effort against the adverse health effects of urbanization. However, there are still research gaps that need to be addressed before the health benefits of greenspaces can be fully integrated into practice.